2010
DOI: 10.1111/j.1476-5381.2010.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased brain damage after ischaemic stroke in mice lacking the chemokine receptor CCR5

Abstract: Background and purpose:The chemokine receptor CCR5 is well known for its function in immune cells; however, it is also expressed in the brain, where its specific role remains to be elucidated. Because genetic factors may influence the risk of developing cerebral ischaemia or affect its clinical outcome, we have analysed the role of CCR5 in experimental stroke. Experimental approach: Permanent cerebral ischaemia was performed by occlusion of the middle cerebral artery in wild-type and CCR5-deficient mice. Locom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 64 publications
2
53
0
Order By: Relevance
“…Moreover, mice carrying mutations of CCR5, the receptor for chemokines CCL3, CCL4, CCL5, CCL8, CCL11, CCL14 and CCL16, show larger cerebral infarct size, with increased neuronal death and neutrophil infiltration associated with behavioural deficits (Sorce et al 2010). The mechanism by which CCR5 reduces secondary damage after CNS injury is not known, although both direct effects on neurons and avoidance of excessive microglial activation have been considered.…”
Section: Ccl3 Ccl4 and Ccl5mentioning
confidence: 98%
“…Moreover, mice carrying mutations of CCR5, the receptor for chemokines CCL3, CCL4, CCL5, CCL8, CCL11, CCL14 and CCL16, show larger cerebral infarct size, with increased neuronal death and neutrophil infiltration associated with behavioural deficits (Sorce et al 2010). The mechanism by which CCR5 reduces secondary damage after CNS injury is not known, although both direct effects on neurons and avoidance of excessive microglial activation have been considered.…”
Section: Ccl3 Ccl4 and Ccl5mentioning
confidence: 98%
“…Of note chemokines and their receptors (such as CCR5) are suggested to be involved in physiological neuroglial communication (Park et al , 2009), neuronal differentiation (Park et al , 2009), and neuronal survival under pro-apoptotic conditions (Meucci et al , 1998). Further, loss of dopaminergic neurons (Choi et al , 2013) and increased brain damage after ischemic stroke (Sorce et al , 2010) has been reported in CCR5-deficient mice. Thus, under certain conditions, loss of CCR5 function (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…CCR5 knockout mice showed increased mortality rates in the pulmonary inflammatory response to influenza A virus infection, which involved accelerated macrophage accumulation in the lung (Dawson et al 2000). Furthermore, CCR5-deficient mice showed increased severity of brain damage after ischemic stroke, which involved increased neutrophil infiltration in the brain (Sorce et al 2010).…”
Section: Introductionmentioning
confidence: 98%